If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) = 3x + -2 Reorder the terms: 4(-3 + 2x) = 3x + -2 (-3 * 4 + 2x * 4) = 3x + -2 (-12 + 8x) = 3x + -2 Reorder the terms: -12 + 8x = -2 + 3x Solving -12 + 8x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 8x + -3x = -2 + 3x + -3x Combine like terms: 8x + -3x = 5x -12 + 5x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 5x = -2 + 0 -12 + 5x = -2 Add '12' to each side of the equation. -12 + 12 + 5x = -2 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = -2 + 12 5x = -2 + 12 Combine like terms: -2 + 12 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| (x-6)(x+9)=x^2 | | 16=n-125 | | 3/4t-2=7 | | (x-6)(x+9)=2x | | X^2+6x+8=0 | | A=zw+z | | -8x^2+9x+7=0 | | p-7=3 | | mn-2p=2 | | 46x/82x | | -19/6+(-5/6) | | 21-y+4=30-6y | | 21z-39=z-(-39) | | 21z-39=z-39 | | b^3m^3-64h^3= | | (15c^-7d^3/35c^5d^7)^-3 | | 44=16+n | | 4x-x^3= | | t(5t^2+3)=0 | | 18+j=94 | | 47-4x=5x+19 | | 17x-4x^3= | | 4953=P(1+(0.03)(9)) | | 5f^12g^-4/f^5g^7 | | 25-p^2y^2= | | k-22=101 | | 2(x+Y)+6Y= | | 21(x-39)=x+39 | | 81-b^4= | | 2/49z^3+1/14z^2 | | 8p^3-h^3= | | 21(x-39)=-39-x |